Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Given f() = -4x + 3, find f(-3)

Sagot :

Answer:

The answer is 15

Step-by-step explanation:

f(x) = -4x + 3, f(-3)

f(-3) = -4x + 3

f(-3) = -4(-3) + 3

f(-3) = 12 + 3

f(-3) = 15

Thus, The answer is 15

Answer:

f(-3)=-4(-3)+3

=12+3=15

Step-by-step explanation:replace x with -3

Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.